DEVELOPMENT OF PHYSICS SELF LEARNING MEDIA USING LECTORA INSPIRE IN THE STATIC FLUID LESSON FOR HIGH SCHOOL STUDENTS X GRADE SCIENCE CLASS - NURJANAH ALFIATI; Suharyanto Suharyanto (Universitas negeri Yogyakarta, 2016)
AbstractThis research is a development research to build a learning media using lectora inspire. The product is used as self learning media which can also be used as additional learning resource. The aim of this research are : (1) to develop learning media using lectora inspire for physics lesson of X grade high school students; and (2) to know the qualification the media as self learning resource. Model used in this research is research and development (RD). Development of learning media is processed based on ten development phases by Walter R. Borg and Merdith Damien Gall. This research is limiting the phases in to six phases, they are : research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, and main field testing. Instruments used in this research are expert evaluation, high school teacher evaluation, and student respons questionnaire. Data analysis to know the qualification of media product and student respons questionnaire are by using conversion into 5 scale value. The result of this research shows that based on evaluation process, this media product of lectora inspire software is qualified to be used and categorized as very good and students also give very good respons to the media as self learning media.Keywords: learning media, lectora inspire, physics learning, students respons